The Depression Anxiety Stress Scale-21 in Chinese Hospital Workers: Reliability, Latent Structure, and Measurement Invariance Across Genders - Jiang, Li-chen; Yan, Ya-jun; Jin, Zhi-Shuai; Hu, Mu-Li; Wang, Ling; Song, Yu; Li, Na-Ni; Su, Jun; Wu, Da-Xing; Xiao, Tao (Frontiers in Psychology, 2020)
The Depression Anxiety Stress Scale-21 (DASS-21) is an instrument in the assessment of mental health status. The current study recruited 1,532 Chinese hospital workers (74.4% female, mean age = 31.97 years, SD age = 9.70) to examine the reliability, latent structure, and measurement invariance of the DASS-21 between genders. The Cronbach’s values were greater than 0.90 for total score. This study examined four possible models of the DASS-21 using the confirmatory factor analysis ( CFA) in Chinese hospital workers. The results from CFA revealed that the latent structure of the DASS-21 in medical staffs is best represented by one-factor model. Then we used the one-factor model to examine measurement invariance across genders by using a multiple-group categorical CFA (MCCFA). All values of RMSEA were less than 0.08, all CFI and TLI values were greater than 0.90, and allΔCFI (the changes in CFI)were less than 0.010 and ΔRMSEA (the changes in RMSEA) were less than 0.015. These fingings supported the gender invariance of the DASS-21 among Chinese hospital workers.